De novo podocytopathy following moderna COVID-19 vaccine: A case report and racial disproportionality in adverse effect reports - Hong, Li-Yu; Lee, Chii-Hong; Chiu, I-Jen (Frontiers in Medicine, 2022)
In this study, we report a case of de novo minimal change disease shortly after the second dose of the Moderna COVID-19 vaccine. A previously healthy 51-year-old Asian man presented with lower-limb edema and foamy urine 3 days after receiving the second dose of the vaccine. Laboratory data revealed the following: serum creatinine, 0.65 mg/dl; serum albumin, 1.3 g/dl; urine protein-to-creatinine ratio, 15.3 g. A renal biopsy was performed, and minimal change in the disease was confirmed. The patient achieved complete remission in the tenth week after starting treatment with prednisolone (1 mg/kg/day). Ethnic differences may influence the adverse effects of drugs and vaccines. However, there is very limited data to address the influence of ethnic diversity on disease prevalence, clinical presentation, and treatment outcomes in COVID-19 vaccine-associated glomerulonephritis.